Effects of Lactobacillus acidophilus and zinc oxide on the growth performance, jejunal morphology and immune function of weaned piglet following an Escherichia coli K88 challenge - Hai-Hua Li; Xian-Ren Jiang; Wen-Jie Wang; Jia-Yun Qiao (Italian Journal of Animal Science, 2018)
This study evaluated the effects of Lactobacillus acidophilus (LA) and zinc oxide (ZnO) supplementation on the growth performance, jejunal morphology and immune function of weaned piglets challenged with Escherichia coli K88. A total of 96 weaned piglets were randomly allocated to four treatments in a 28-day experiment with a 2 × 2 factorial experiment involving two levels of L. acidophilus (0 and 5 × 1010 CFU/kg feed), and two levels of ZnO (0 or 3000 mg/kg feed). One piglet per pen was chosen and orally challenged with Escherichia coli K88 on day 28 and slaughtered at 6 hours post-infection. The results showed that LA supplementation increased the average daily gain from day 0 to day 28 (p = .025). Piglets fed with the diets containing LA or ZnO showed lower feed conversion ratio than the unsupplemented group (p < .05). In addition, LA supplementation increased villus height (VH), villus width and the ratio of VH and crypt depth (CD) compared to the unsupplemented group (p < .001). Administration of ZnO increased VW (p = .001) and VH:CD ratio (p = .039). Moreover, dietary LA and ZnO upregulated the mucin 2 and β-defensin 3 expression in the jejunum (p < .001), and LA supplementation increased immunoglobulin A concentration in the jejunal tissue (p = .019). In conclusion, the administration of LA or ZnO was effective in improving growth performance of weaned piglets, and both supplementations may benefit the jejunal development and immune function of piglets following E. coli K88 challenge.